Role of diffusion-annealing time on the superconducting, microstructural and mechanical properties of Cu-diffused bulk MgB2 superconductor - Doğruer, Musa; Görür, Osman; Zalaoğlu, Yusuf; Öztürk, Özgür; Yıldırım, Gürcan; Varilci, Ahmet; Terzioğlu, Cabir (Springer Science and Business Media LLC, 2012)
In this study, the effect of various annealing time (0.5, 1, 1.5 and 2 h) on microstructural, mechanical and superconducting properties of the Cu-diffused bulk MgB2 superconducting samples is investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM), Vickers microhardness (H v ) and dc resistivity measurements for the first time. The critical transition temperature, grain size, phase purity, lattice parameter, surface morphology, crystallinity and room temperature resistivity values of the bulk samples prepared are compared with each other. Electrical-resistivity measurements show that the sample (annealed at 850 °C for 1 h), exhibiting the highest room temperature resistivity, obtains the maximum zero resistivity transition temperature (T c ). From the XRD results, all the samples contain MgB2 as the main phase with a very small amount of Mg2Cu phase. Moreover, SEM investigations conducted for the microstructural characterization illustrate that not only does the grain size of the samples studied enhance gradually, but the surface morphology and grain connectivity also improve with the increase in the diffusion-annealing time up to 1 h beyond which all the properties obtained start to degrade. Indeed, the worst surface morphology is observed for the Cu-diffused bulk MgB2 superconductor exposed to 2 h annealing duration. At the same time, Vickers microhardness, elastic modulus, load independent hardness, yield strength, fracture toughness and brittleness index values are calculated separately for the pure and Cu-diffused samples. It is found that the microhardness values depend strongly on the diffusion-annealing time. Furthermore, the diffusion coefficient of the Cu ion in the bulk MgB2 superconductor is obtained to change from 1.63 × 10−7 to 2.58 × 10−7 cm2 s−1. The maximum diffusion coefficient is observed for the sample prepared at 850 °C for 1 h whereas the minimum one is noted for the sample annealed at 850 °C for 2 h, confirming that the annealing-time of 1 h is the best ambient to improve the mechanical, microstructural and superconducting properties of the samples produced.